Cerebral air embolism as a complication of peptic ulcer in the gastric tube: case report - Suzuki Takahisa (BMC Gastroenterology, 2011)
Abstract Background The reported incidence of ulcer formation in the gastric tube in esophageal replacement is rare. Case Presentation This is the first report of a case of cerebral air embolism as a result of spontaneous perforation of an ulcer in the constructed gastric tube into the pulmonary vein during post-operative follow-up in a patient with esophageal cancer. Conclusions Cerebral air embolism is a rare complication of penetrating gastric ulcer, but should be considered in patients with a history of esophagectomy with gastric conduit that present with acute neurologic findings.